The labour theory of value, and the double transformation problem - Guerrero, Diego (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
If there is a “transformation” from direct prices (w) into production prices (p), it should be a second one from production prices into market prices (m). Market prices are the great oblivion of the whole literature on the labour theory of value (LTV) and the Transformation Problem (TP). When these prices are taken seriously into consideration, one needs to deal with three equations of values-prices, not two, and market prices must appear in the right side of all of them. As a consequence, the conventional expressions of values and prices become wrong included those of the New Interpretation (NI) and the Temporal Single System (TSS). As a further result, all Marxian totals—the total value of the output and the total surplus-value, among others—remain invariable through both transformations, and there is just one single rate of surplus-value and one single rate of profit. The “temporal” equations used by the TSS are also misguided since time should be treated in another way according to which the static equations are compatible with a dynamic approach. Lastly, a summarized history of the historical debate on this issue helps to see that this approach, as the most general one, can shelter as particular cases the prevailing views.